THE INFLUENCE OF SELF-REGULATION ON ACADEMIC PROCRASTINATION WITH SOCIAL MEDIA FOMO AS A MODERATOR - Sari, Rini Puspita; Septiana, Nila Zaimatus; Fernanda, Jerhi Wahyu (Jurusan Bimbingan dan Konseling, 2025)
Academic procrastination is one of the problems experienced by students in learning and is often associated with self-regulation and FOMO on social media which can be a contributing factor. This study aims to determine the influence of self-regulation on academic procrastination with FOMO on social media as a mediating variable. This study uses a quantitative approach with the ex post facto correlation method and Structural Equation Modeling (SEM) analysis to analyze the data. Sampling was carried out using a cluster random sampling technique, with a sample of 190 eighth grade students at MTsN 1 Kota Kediri. The results of the study show that (1) self-regulation influences FOMO on social media with a P value (0.000) < 0.05 and a β value = -0.665; (2) self-regulation influences academic procrastination in SKI subjects with a P value (0.000) < 0.05 and a β value = -0.576; (3) FOMO on social media has no influences on academic procrastination with a P value (0.666) > 0.05 and a β value = 0.057; and (4) self-regulation has no influences on academic procrastination in SKI subjects with FOMO on social media as a mediating variable with a P value (0.667) > 0.05 and a β value = -0.199